Comparative Evaluation of Periapical Lesions Using Periapical Index Adapted for Panoramic Radiography and Cone Beam Computed Tomography - KESER, GAYE; NAMDAR PEKİNER, FİLİZ MEDİHA (AVES PRESS LTD, 2018)
Objective: The aim of this retrospective study was to comparatively evaluate periapical lesions using the periapical index adapted for panoramic radiography and cone beam computed tomography (CBCT-PAI). Methods: The study group consisted of pre-existing panoramic radiographs and CBCT records of 200 individuals (100 women and 100 men). In this study, panoramic radiographs were evaluated using the PAI scoring system, which uses a scale from 1 to 5 with an increasing radiographic periapical status degree. CBCT images were evaluated using the CBCT-PAI scoring system, which includes two additional variables that indicate any possible expansion or destruction of the cortical bone. During statistical evaluation, the relationship between PAI and CBCT-PAI was investigated by Spearman's rho correlation analysis. Results: In our study, there was no significant difference between the mean ages according to gender (p>0.05). Moreover, there was no significant difference between the numbers of teeth with lesions according to gender (p>0.05). A significant and positive correlation was found between PAI and CBCT-PAI scores in all samples in coronal, sagittal, and axial planes (p<0.01). Conclusion: It was confirmed that CBCT provides more accurate information about the extension and dimensions of periapical lesions.
Keywords: Periapical lesions; cone beam computed tomography; radiography; panoramic; APICAL PERIODONTITIS; CORONAL RESTORATIONS; ENDODONTIC TREATMENT; POPULATION; PREVALENCE; DIAGNOSIS; ADULT; MANAGEMENT; FILLINGS; QUALITY